(untitled) (Eastern Medical College Journal, 2025)
Background: A growing and serious concern for public health in both developed and developing nations is antimicrobial resistance (AMR). AMR monitoring and control are especially difficult in underdeveloped nations due to several factors, such as a lack of surveillance systems, a lack of money, inadequate compliance with infection control protocols, careless use of antibacterial formularies and medications. Methodology: This study conducted a comprehensive assessment of AMR prevalence within a tertiary-level medical facility over a one-year period, examining 1344 samples. Results showed that 219 (16.3%) of samples exhibited significant growth of resistant organisms. Results: Our samples were Pus/wound swabs 103 (47.05%) and urine samples 101 (46.11%) had the highest proportions of resistance. Blood 03 (1.37%) and sputum 03 (1.37%) showed lower resistance rates. Escherichia coli (E. coli) was the most prevalent resistant organism, with 52 instances, followed by Methicillin-Sensitive Staphylococcus aureus (MSSA) with 47 instances. Klebsiella demonstrated a diverse presence (43 instances), and MRSA exhibited 24 instances. Co-trimoxazole 132 (60.27%), Ampicillin/Amoxicillin 107 (48.86%), and Fluoroquinolones 123 (56.16%) faced the highest resistance frequencies. A significant 155 (71%) of specimens were collected after the administration of antibiotics, pointing to a crucial area requiring enhancement in terms of specimen collection timing. Noteworthy 131 (60%) of participants remained uncertain about their prior antibiotic usage, underscoring the importance of more comprehensive historical data documentation and heightened patient education initiatives. It’s notable that none of the self-medicated patients successfully completed their treatment, while only a minimal 03 (1.36%) of prescription-based patients managed to adhere to their prescribed regimen. Conclusion: This underscores the critical need for vigilant adherence monitoring and patient support to address this concerning issue. Antimicrobial resistance rates are high and pose a serious therapeutic challenge to the management of common infections. Eastern Med Coll J. July 2025; 10 (1): 57-64